PENGEMBANGAN MEDIA PEMBELAJARAN FLIPBOOK DENGAN MODEL PEMBELAJARAN PROBLEM BASED LEARNING UNTUK MENINGKATKAN HASIL BELAJAR MUATAN PELAJARAN IPS PADA SISWA KELAS V SD NEGERI 2 SINGOROJO KABUPATEN KENDAL - Dharma Fauzan Nabil Huwaidi; Isa Ansori (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This research examines the development of Flipbook learning media paired with the Problem Based Learning (PBL) learning model in improving grade V IPAS learning outcomes. The type of research used is Research and Development (R&D). the research subject used 19 fifth grade students of SD Negeri 2 Singorojo, Kendal Regency. The results of the student pretest and posttest, the average score of the small group was 46.6 and the subsequent test was 93.3. The average score of the large group test was 43 and the final score was 92.5. The results in this study concluded that flipbook media is very feasible to use in the learning process in social studies lessons and is able to improve the social studies learning outcomes of fifth grade students of SD Negeri 2 Singosari Kendal Regency.